2018
DOI: 10.3168/jds.2017-13236
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of plasma branched-chain amino acid concentrations during glucose infusion directs essential amino acids to extra-mammary tissues in lactating dairy cows

Abstract: The objectives of this study were to investigate the effects of branched-chain AA (BCAA) supplementation when glucose is infused postruminally into lactating dairy cows consuming a diet low in crude protein (CP) and to test the hypothesis that low BCAA concentrations are responsible for the poor stimulation of milk protein yield by glucose. Twelve early-lactation Holstein cows were randomly assigned to 15% and 12% CP diets in a switchback design of 6-wk periods. Cows consuming the 12% CP diet received 96-h con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 42 publications
(71 reference statements)
4
21
0
Order By: Relevance
“…This can be achieved for instance by exploiting the list of reactions belonging to the sub-network connecting the discriminant metabolites (see supplementary table S5). Nevertheless, it has been reported that increased levels of rumen propionic acid (see below) and glucose, as has been observed in this work, are associated with lower concentrations of branched-chain amino acids in cows plasma 43,44 .…”
Section: Discussionsupporting
confidence: 58%
“…This can be achieved for instance by exploiting the list of reactions belonging to the sub-network connecting the discriminant metabolites (see supplementary table S5). Nevertheless, it has been reported that increased levels of rumen propionic acid (see below) and glucose, as has been observed in this work, are associated with lower concentrations of branched-chain amino acids in cows plasma 43,44 .…”
Section: Discussionsupporting
confidence: 58%
“…These observations are in agreement with studies that reported a decrease in p[BCAA] when dairy cows were fed starchy diets (Cantalapiedra-Hijar et al, 2014), when glucose was infused intravenously (Toerien et al, 2010;Curtis et al, 2014Curtis et al, , 2018 or postruminally (Hurtaud et al, 1998;Lemosquet et al, 2009;Nichols et al, 2016), or when a gluconeogenic substrate was infused in the rumen (propionate; Raggio et al, 2006;Lemosquet et al, 2009) or postruminally (starch; Rius et al, 2010a). The suppressive effect of increased energy supply on p[BCAA] is associated with increased insulin secretion (Rius et al, 2010a;Nichols et al, 2016), an effect well demonstrated during the hyperinsulinemiceuglycemic clamp technique in dairy cows (Laarveld et al, 1981;Griinari et al, 1997;L'Espérance, 2000;Mackle et al, 2000) and other species (Castellino et al, 1990;Tesseraud et al, 1992;Bequette et al, 2001).…”
Section: Plasma Concentrations Of Isoleucine Leucine and Valine In supporting
confidence: 92%
“…When combined with infusions of casein or AA mixtures, glucose or glucose precursors stimulate milk protein yield in some studies (Raggio et al, 2006;Rius et al, 2010a), but not in all (Clark et al, 1977;Nichols et al, 2016). However, when circulating AA levels are abundant, exogenous glucose appears to have an effect on AA storage in extra-mammary tissues rather than on the stimulation of milk protein synthesis (Clark et al, 1977;Nichols et al, 2016;Curtis et al, 2018), possibly through the anabolic action of insulin on skeletal muscle (Lobley, 1998) and adipose (Griinari et al, 1997). In agreement with this hypothesis, 13% of N intake was retained on HMP-GG, compared with 6% on HMP-C, with no appreciable change in milk N output (1% of N intake) between treatments.…”
Section: Energy and N Partitioningmentioning
confidence: 99%
“…However, increasing glucogenic energy at low and high levels of protein supply can improve postabsorptive AA transfer efficiency from the gut to milk protein by reducing AA catabolism across the gut and the splanchnic bed, potentially improving mammary gland supply (Rius et al, 2010b). In combination with high circulating AA levels, glucogenic energy may also support N retention by stimulating AA partitioning toward extra-mammary tissues (Clark et al, 1977;Nichols et al, 2016;Curtis et al, 2018).…”
Section: Introductionmentioning
confidence: 99%